Wer bezahlt, bestellt: (Un-)Abhängigkeiten der Medieninhalte von der Medienfinanzierung - Lewinski, Kai von (Schriften zum Medien- und Informationsrecht, 2017)
The media needs to be independent, but it also needs funding. Money, however, is rarely given without expecting a return service, or at least without strings attached. Readers only pay for what they want; advertisements are only booked in matching context, and public broadcasters are fighting for the acceptance of their contribution-based funding. New forms of financing, such as crowd funding, donations and new public-law creations, are attempts to counteract this interdependency of media content and media funding. However, these new forms of financing also entail new (and old) interdependencies.This documentation of a conference at the University of Passau attempts to examine this hypothesis of the (inevitable) dependency of content on funding. Aiming for an independent media sector, individual and, especially, innovative forms of financing are discussed and illustrated.
Gesehen am 03.01.2018. - Aus dem Vorwort: Am 16. und 17. November 2016 fand an der Universität Passau die Tagung "Wer bezahlt, bestellt - (Un-)Abhängigkeiten der Medieninhalte von der Medienfinanzierung" statt
Keywords: Konferenzschrift -- 16.11.2016-17.11.2016 -- Passau; Medienrecht; Werbeeinnahmen; Unabhängigkeit; Massenmedien; Deutschland